Association of Nonalcoholic Fatty Liver Disease and Venous Thromboembolism in Women With Endometrial Cancer. (November 2017) - Moeini, Aida; Machida, Hiroko; Takiuchi, Tsuyoshi; Blake, Erin A.; Hom, Marianne S.; Miki, Toshio; Matsuo, Osamu; Matsuo, Koji
Objective: Recent studies have demonstrated that surgical menopause results in a significantly increased risk of nonalcoholic fatty liver disease (NAFLD) in women with endometrial cancer. In addition, venous thromboembolism (VTE) is known to be one of the major prognostic factors for decreased survival in endometrial cancer. Given the fact that coagulation factors are produced in the liver, the correlation between NAFLD and VTE was examined in endometrial cancer. Methods: A retrospective study was conducted to examine patients with endometrial cancer who underwent surgical staging including oophorectomy between 2000 and 2013 (n = 714). Cumulative risk of VTE was examined based on the NAFLD status. A Cox proportional hazard regression model was used to determine the independent risk predictors of VTE. Results: Venous thromboembolism and NAFLD were seen in 57 (8.0%) and 181 (25.4%) cases, respectively. Two-year cumulative risks of VTE and NAFLD were 7.9% and 19.3%, respectively. In univariate analysis, VTE was significantly associated with decreased disease-free survival (2-year rate, 43.6% vs 91.4%, P < .001) and overall survival (65.8% vs 96.8%, P < .001), whereas NAFLD was associated with decreased risk of VTE (1.7% vs 10.4%, P < .001). In multivariate analysis controlling for clinicopathological factors, NAFLD remained an independent predictor of decreased risk of VTE (hazard ratio [HR]: 0.24, 95% confidence interval [CI]: 0.07-0.79, P = .02). Thrombocytosis (HR: 2.30, 95% CI: 1.22-4.35, P = .01), cancer antigen 125 ≥ 35 (HR: 3.81, 95% CI: 1.78-8.17, P < .001), and recurrent disease (HR: 4.57, 95% CI: 1.97-10.6, P < .001) remained as independent predictors of increased risk of VTE. Conclusion: Our results suggest that NAFLD may be associated with decreased VTE risk in women with endometrial cancer.